Socioeconomic Inequities in Vaccine Hesitancy Among Native Hawaiians and Pacific Islanders (Mary Ann Liebert, 2022)
Purpose: COVID-19 vaccine hesitancy exists in communities of color who are disproportionately impacted by COVID-19. In many states, Native Hawaiians and Pacific Islanders (NHs/PIs) experience the highest rates of COVID-19 confirmed cases and mortality among U.S. ethnic/racial groups. National trends regarding vaccine hesitancy among NHs/PIs are currently lacking. Methods: Data were derived from the Asian American and NH/PI COVID-19 Needs Assessment Project, a national survey conducted during January?April 2021. The final analytic sample included 868 NH/PI adults. Logistic regression analyses were conducted to estimate odds ratios for vaccine hesitancy. Results: Vaccine hesitancy ranged from 23% among Other PIs to 56.3% among Tongan adults. Younger adults (18?24 and 25?44 years), those with lower educational attainment, and those with lower income were more vaccine hesitant. Overall, education and income showed a strong association with vaccine hesitancy in bivariate logistic models. However, the associations between vaccine hesitancy and education and income varied by NH/PI groups. NHs, Samoans, and Multiethnic NHs/PIs showed the most consistent associations between the socioeconomic position variables and vaccine hesitancy. Conclusions: The examination of vaccine hesitancy among NHs/PIs follows the socioeconomic gradient for some ethnic groups but not others. More studies are needed to determine what other socioeconomic indicators may be associated with health among specific NH/PI ethnic groups. Policy Implications: Reforms are needed to overcome structural racism underlying NH/PI evidence production, which currently renders NHs/PIs invisible. Innovative solutions based on successful community efforts can help deconstruct racist data inequities experienced by NHs/PIs.